Lycopene: Food Sources, Biological Activities, and Human Health Benefits. (19th November 2021) - Khan, Usman Mir; Sevindik, Mustafa; Zarrabi, Ali; Nami, Mohammad; Ozdemir, Betul; Kaplan, Dilara Nur; Selamoglu, Zeliha; Hasan, Muzaffar; Kumar, Manoj; Alshehri, Mohammed M.; Sharifi-Rad, Javad
Abstract : As an antioxidant, lycopene has acquired importance as it prevents autoxidation of fats and related products. Tomatoes are an important agricultural product that is a great source of lycopene. It contains many vitamins and minerals, fiber, and carbohydrates and is associated with various positive effects on health. The antioxidant potential of tomatoes is substantially explained with lycopene compounds. Diet is a major risk factor for heart diseases which is shown as the most important cause of death in the world. It has been observed that the lycopene taken in the diet has positive effects in many stages of atherosclerosis. The serum lipid levels, endothelial dysfunction, inflammation, blood pressure, and antioxidative potential are mainly affected by lycopene. These natural antioxidants, which can also enhance the nutritional value of foods, may lead to new ways if used in food preservation. In this review study, the antioxidant potential and cardiovascular protection mechanism of lycopene are discussed.